The effect of machining and induced surface deformation on the fatigue performance of a high strength metastable β titanium alloy. (July 2019) - Cox, A.; Herbert, S.; Villain-Chastre, J.-P.; Turner, S.; Jackson, M.
Highlights: Four point fatigue testing is effectively determines machining subsurface deformation. Bespoke machining and fatigue testing technique is applicable to a range of aerospace materials. Increased metal removal rates of 50% reduced of cycles to failure in low cycle failure mode by 50%. Dominant crack initiation in Ti-5553 is alpha basal planes at the machined subsurface. Modifications to the upstream forging prior to machining could increase Ti-5553 service life. Abstract: Metastable beta titanium alloys such as Ti-5Al-5Mo-5V-3Cr (Ti-5553) are used for large aero-structural components. During processing these alloys are subject to costly machining operations. There is an industry demand to machine at improved metal removal rates (MRR) to meet increasing aircraft orders. To understand the effects of MRR on subsurface deformation and fatigue performance, fatigue coupons were end milled under two different industrial conditions. The surface roughness, residual stress and subsurface deformation was characterised and a custom four point bend fatigue testing was designed to determine the effect of MMR on cycles to failure. The study has demonstrated that an increase in MMR of 50% resulted in a LCF reduction of 57.37%. This was a direct result of increased subsurface damage and residual stresses.